Determinants of Teachers’ Attitudes Towards E-Learning in Tanzanian Higher Learning Institutions - Kisanga, Dalton (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2016)
This survey research study presents the findings on determinants of teachers’ attitudes towards e-learning in Tanzanian higher learning institutions. The study involved 258 teachers from 4 higher learning institutions obtained through stratified, simple random sampling. Questionnaires and documentary review were used in data collection. Data were analysed using statistical package for the social sciences (SPSS). Chi-square was performed to examine the association of variables.It was found that teachers have positive attitudes towards e-learning where computer exposure played a statistically significant contribution to their attitudes. It is recommended that training in e-learning needs to be provided to teachers to widen their understanding of e-learning. There is also a need to strengthen factors associated with teachers’ positive attitudes towards e-learning. Results from this study are of particular importance to both teachers and the education stakeholders in Tanzania.